Performance of a Hybrid PV/T Thermosyphon System - Kalogirou, Soteris A.; Tripanagnostopoulos, Yiannis (My University, 2005)
Hybrid Photovoltaic/Thermal (PV/T) units are systems capable of producing both electrical and thermal energy in a single unit. Thermosyphon units are solar systems employing flatplate collectors which are suitable for low temperature applications, like domestic hot water production. In this paper a hybrid PV/T thermosyphon system is modeled and simulated with TRNSYS program. The system’s hybrid collectors are glazed, 4m2 in area and the hot water storage tank is 160 liters. Both polycrystalline and amorphous silicon solar cells are considered. The system is simulated on an annual basis at three different locations, Nicosia, Cyprus; Athens, Greece and Madison, Wisconsin. The results show that the electrical production of the system, employing polycrystalline solar cells, is 532 kWh, 515 kWh and 499 kWh and the solar thermal contribution is 0.686, 0.564 and 0.293 for the three locations respectively. The respective results for the system employing amorphous silicon cells are 260 kWh, 251 kWh, 224 kWh and 0.726, 0.601 and 0.341 for the three locations respectively. A non hybrid PV system produces about 30% more electrical energy but the present system covers also, depending on the location, a large percentage of the hot water needs of a house.
Keywords: Hybrid Photovoltaic/Thermal (PV/T); Thermosyphon system